Obtenção de pigmentos à base de cinzas de algaroba e cajueiro, impregnados com íons cobalto e cobre, para aplicação em esmaltes cerâmicos - Davi, Ana Paula Caldas (Universidade Federal Rural do Semi-Árido, 2020)
In the countryside of Rio Grande do Norte, there is a large production of red ceramics, and there is also the artisanal production (potteries), which uses biomass as an energy source. According to the National Energy Balance of the Ministry of Mines and Energy, the consumption of biomass as an energy source corresponds to 8.3% of the Brazilian energy matrix. In the sector composition, the consumption of biomass by the ceramic industry corresponds to 3.0% of the total consumed in the whole country. Biomass ash is the solid residue resulting from complete or incomplete combustion of biomass and represents a heterogeneous mixture of variable composition with organic and inorganic components. From the viewpoint of the technological use of these ashes, this work aims to take advantage of the residual ash from the burning of the biomass of algaroba and cashew tree, to produce alternative ceramic pigments. The development of ceramic pigments is important, since most of the pigments consumed by the Brazilian ceramic industry are imported from European countries. The residual ash was obtained from a pottery sector in the Assu’s Valley ceramic pole, located in the interior of the state of Rio Grande do Norte. The pigments were prepared by impregnating the cobalt and copper ions in the residual ash by means of a wet process. The samples were calcined at temperatures of 700ºC and 900ºC and used to color transparent gloss enamel. The enamels were applied on ceramic pieces and sintered at temperatures of 1100 and 1150ºC. The techniques of X-ray fluorescence characterization, X-ray diffraction, scanning electron microscopy, UV- Visible spectroscopy and colorimetric analysis were used. In the commercial enamel, the pigments obtained using cobalt as chromophore ion presented lilac tones to dark blue. The pigments obtained using copper, presented light green tones. Wet incorporation has proved viable for the production of pigments derived from residual ash
Keywords: Biomassa; Cinza residual; Colorimetria; Impregnação; Pigmentos inorgânicos; Biomass; Residual ash; Colorimetry; Impregnation; Inorganic pigments; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA